Rabbit Redux - Updike, John. (London : Penguin Books, 2006)
In 1969, the times are changing in America. Things just aren't as simple as they used to be for Rabbit Angstrom. His wife leaves him, and suddenly, into his confused life comes Jill, a runaway who becomes his lover. But when she invites her friend to stay, a young black radical named Skeeter, the pair's fragile harmony soon begins to
Keywords: Angstrom, Harry (Fictitious character) -- Fiction; Middle class men -- Fiction; Angstrom, Harry (Fictitious character).